Investigation of SIW directional coupler for 60ghz mm-wave applications - Bharath Kumar, K.; Shanmuganantham, T. (International Journal of Engineering and Technology, 2018)
In this article, 60 GHz directional coupler is designed by using Substrate Integrated Waveguide (SIW) technology using Coplanar waveguide as a transmission path. To design directional coupler RT duriod 5880 substrate material is used. Here directional coupler is analyzed by changing the thickness of copper coating and height of the substrate. By changing the thickness of copper coating and height of substrate examining the directional coupler results like reflection coefficient, insertion loss, coupling factor, isolation loss, VSWR, surface current, Electric field and magnetic field variations. Verifying the thickness and height of substrate is suitable for RADAR application in millimeter frequency range. RT duriod 5880 substrate material height is 0.508mm and thickness of 0.035mm are chosen to design directional coupler. At 60 GHz directional coupler gives reflection coefficient as -36.03 dB, insertion loss as -1.3 dB, coupling factor of -6.3 dB and isolation loss of -36 dB.